Passionate hearts, torn loyalties: navigating the interplay between fandom and romance - Levental, Orr; Lev Arey, Dalit; Lev, Assaf (Frontiers in Psychology, 2023)
The current study presents a thorough investigation of the attitudes and emotions expressed by the spouses and girlfriends of sports fans within the context of their longterm relationships. Its primary objective is to explore the potential ramifications that surface when individuals become deeply invested in a competitive sport, demonstrating intense emotional connections, broad knowledge, unwavering loyalty, and active engagement in fan-related activities. The research methodology applied in this study involved conducting semi-structured interviews with a sample of twelve spouses and girlfriends of fans. The principal findings elucidate four distinct themes that shed light on the intersection of fandom and romantic relationships. These themes include: "that's what I signed up for"; "fandom as a gendered activity"; "the good, the bad, and the ugly"; and "sports fandom as an addiction." The study concludes by highlighting the crucial cultural context at work. The social criticism expressed by the interviewees towards non-traditional gender behaviors displayed by their partners serves as a cautionary message. These criticisms aim to preserve and uphold male dominance in sports, thereby reinforcing the notion of their unquestioned supremacy. Consequently, we argue that, within this context, latent aggressive behavior in men is perceived as a strategy to maintain their monopolistic control over sports domains.